The PENGARUH EDUKASI ONLINE MENGGUNAKAN BUKU KIA TERHADAP PENGETAHUAN TANDA BAHAYA IBU HAMIL DI PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Dila Safitri; Siti Zakiah Zulfa (Jurnal Medicare, 2025)
The high maternal mortality rate in Indonesia remains a serious concern, partly due to pregnant women’s lack of knowledge about danger signs during pregnancy. This study aims to examine the effect of online education using the Maternal and Child Health (MCH) Book on pregnant women's knowledge of danger signs at Payung Sekaki Health Center in Pekanbaru City. A pre-experimental design with one group pre-test and post-test was applied. The sample consisted of 44 pregnant women selected by total sampling. Education was conducted online via WhatsApp, using material from the MCH Book. The Wilcoxon test showed a significant increase in knowledge after the intervention (p < 0.05). These findings indicate that online education based on the MCH Book is effective in increasing pregnant women's understanding of pregnancy danger signs. This method can be considered an alternative approach for maternal health education to prevent pregnancy complications.